Relief supply in the aftermath of the 2009 typhoon morakot - Liao, Yen-Hsiung (International Journal of Health, 2014)
Purpose: To monitor whether the relief including food, and supplies met the need for the Typhoon Morakot victims. Approach: Relief data was obtained from the Relief Coordination Center (RCC), Pingtung County Government during July 10 to July 28, 2009. The relief was classified into food and supplies categories. Results: The most need of relief was cleaner necessaries (8/15 = 53.3 %), the last need of relief was seasoning (0/15 = 0 %). The subjects including eggs, bread, cloths, socks, lighter, and candle were not required by the victims although they were donated by people. Conclusion: The several catchment areas in Pingtung County needed to be cleaned after the flooding. Therefore, the kind of cleaner necessaries was the most as well as the longest need of relief expectantly. Our results suggest the priorities of resources allocation for the next disaster. Keywords: Typhoon Morakot, Cleaner Necessaries, Resource Allocation.